Adaptive frequency optimization control strategy of electric vehicles participation in energy storage considering user active response margin - Li Cai; Chenxi Yang; Qingshan Xu; Leida Li; Zhen Gao; Juan Yan; Congwen Wang (International Journal of Electrical Power & Energy Systems)
Electric vehicles have steadily emerged as important resources for flexible frequency management in the power grid due to their energy storage capabilities and quick ability to respond. To address a series of operational issues arising from the large percentage of distributed power supply connected to the distribution network, an adaptive frequency optimization control strategy is proposed for EVs participating in energy storage, taking into account the user’s active response margin. Firstly, based on the vehicle’s dynamic features, the user active response margin is suggested to fully utilize the EVs’ participating energy storage capacity. Secondly, the framework of frequency optimization control proposes margin adaptive droop control. It refers to the exploration of the potential storage capacity margin of EVs, enabling the power grid dispatching center to automatically adjust EVs’ charging and discharging power according to the active response of users, thereby achieving the purpose of stabilizing the power grid frequency. On this basis, combined with the improved automatic generation control link, the power distribution between the EV and each generator set is optimized to form an adaptive frequency optimization control strategy. Finally, as shown in the simulation results, the proposed strategy can lessen the frequency shift from various dimensions, resulting in a 73.2% decrease in overshoot and an increase of 5.86% and 0.40% in average rise time and average settling time, respectively. Meanwhile, EVs’ energy storage capacity is enhanced, and user frequency regulation’s incentive revenue has risen by 62.97%. This strategy can be applied in the frequency regulation pilot of virtual power plants and has practical application value for building a new type of power system integrating power sources, grids, loads and storage.